Extremum principles for nonpotential and initial-value problems - Telega, J.J. (Archives of Mechanics, 2002)
The aim of this paper is to derive extrernum and saddle-point principles for a class of nonpotential and initial-value problerns. The procedure used is based on an extension of the procedure primarily used by BREZIS and EKELAND [7,8] to classical parabolic equations. In essence, this approach exploits some fundamental notions of convex analysis.